Economic Recovery : Conversation with David Malpass, Kristalina Georgieva, and Janet Yellen - Malpass, David (World Bank, Washington, DC, 2021)
World Bank Group President David Malpass spoke about the world facing major challenges, including COVID, climate change, rising poverty and inequality and growing fragility and violence in many countries. He highlighted vaccines, working closely with Gavi, WHO, and UNICEF, the World Bank has conducted over one hundred capacity assessments, many even more before vaccines were available. The World Bank Group worked to achieve a debt service suspension initiative and increased transparency in debt contracts at developing countries. The World Bank Group is finalizing a new climate change action plan, which includes a big step up in financing, building on their record climate financing over the past two years. He noted big challenges to bring all together to achieve GRID: green, resilient, and inclusive development. Janet Yellen, U.S. Secretary of the Treasury, mentioned focusing on vulnerable people during the pandemic. Kristalina Georgieva, Managing Director of the International Monetary Fund, focused on giving everyone a fair shot during a sustainable recovery. All three commented on the importance of tackling climate change.